The Impact of Business Training, Motivation, and Technology Usage on Business Innovation - Syamsudin, Syamsudin; Hendayana, Yayan (Dinasti Publisher, 2024)
This study aims to analyze the influence of business training, motivation, and technology usage on business innovation. With increasing competition in the business world, the ability to innovate has become a critical factor for business sustainability. The purpose of this article is to construct hypotheses about the relationships between variables to be used in subsequent research. The research is based on online literature, including Google Scholar, Mendeley, and other academic online resources. The method employed is library research sourced from e-books and open-access e-journals, analyzed using qualitative descriptive methods.. The following are the findings of the analysis: 1) Business training positively impacts business innovation; 2) Motivation drives individuals and organizations toward innovative practices; 3) Technology usage is a major catalyst for business innovation